Sex-specific differences in the association between triglyceride glucose index and carotid plaque in a cardiovascular high-risk population: a cross-sectional study based on a Chinese community-dwelling population - Lin, Weiguo; Xu, Mengjie; Zheng, Jinbiao; Sun, Ruixue; Yan, Shaorong; Chen, Xiaoshu; Lin, Yuzhan (Frontiers in Cardiovascular Medicine, 2024)
Background To date, numerous studies have investigated the relationship between the triglyceride glucose (TyG) index and carotid plaques, but the impact of gender on this relationship has not been explored. Therefore, this study aims to investigate gender-specific differences in the relationship between the TyG index and carotid plaques in a high cardiovascular risk population in China. Methods This cross-sectional study's data were derived from a longitudinal pilot study involving 1,085 high-risk cardiovascular subjects. A multivariable logistic regression model was used to analyze the relationship between the TyG index and carotid plaques. A generalized additive model combined with a stratified regression model was employed to assess the nonlinear relationship between the TyG index and carotid plaques across different genders. In the nonlinear relation, the inflection point was calculated by a two-piecewise linear regression model. Results After adjusting for confounders such as age, sex, BMI, SBP, DBP, AST/ALT, TC, LDL-c, HDL-c, creatinine, smoking, and antilipemic medication, the generalized additive model results revealed a nonlinear relationship between the TyG index and carotid plaque formation, with significant differences across genders. In males, the relationship between the TyG index and carotid plaques was S-shaped. The two-piecewise linear regression model identified two inflection points: TyG = 8.39 (P = 0.017) and TyG = 10.2 (P = 0.009). Conclusion The relationship between the TyG index and the formation of carotid plaques is nonlinear, and there are significant differences in the correlation between males and females.